Using Video-Based Simulations to Foster pPCK/ePCK—New Thoughts on the Refined Consensus Model of PCK - Marie Irmer; Dagmar Traub; Marina Böhm; Christian Förtsch; Birgit J. Neuhaus (Education Sciences, 2023)
This article aims to investigate relationships between the different realms of PCK by referring to the refined consensus model of PCK. We conducted a pre–post study with an intervention using a video-based simulated learning environment to measure different realms of PCK of 78 pre-service biology teachers. The participants were randomly assigned to three groups receiving different treatments in the form of scaffolds while working on the learning environment during the intervention. Only the participants receiving scaffolds referring to their personal PCK significantly improved from the pre-test to the post-test (FpPCK(1,27) = 9.592, p = 0.005, partial η2 = 0.262, n = 28). These scaffolds encourage participants to use their prior knowledge when reflecting on instructional quality, as shown in the simulation. Although the findings of the present study support the theoretical view of the refined consensus model of PCK, more focus on the personal PCK could be helpful to understand how PCK is acquired and organized “within one teacher”.